Pengaruh Promosi Dan Kelengkapan Produk Terhadap Keputusan Pembelian (Survei Pada Konsumen Prianka.Gallery Tasikmalaya) - Mila Siti Karmila; Suci Putri Lestari; Dudu Risana (Transformasi: Journal of Economics and Business Management, 2023)
This study aims to determine the simultaneous and partial effect of Promotion and Product Completeness on Purchase Decisions at Prianka.Gallery Tasikmalaya. The research method used in this study is the causality method with a survey approach. The population in this study is not known with certainty. The sampling technique in this study used Acidental Sampling with a total sample of 100 people who were Prianka.Gallery Tasikmalaya consumers. The type of data used is primary data obtained from questionnaires. The data testing technique used in this study uses validity, reliability, and classical assumption tests. Data analysis in this study used multiple regression analysis using SPSS version 25. The results showed that Promotion and Product Completeness simultaneously influenced Purchase Decisions at Prianka.Gallery Tasikmalaya. Promotion partially has a significant effect on purchasing decisions at Prianka.Gallery Tasikmalaya. Product Completeness partially has a significant effect on Purchasing Decisions at Prianka.Gallery Tasikmalaya.